2017
DOI: 10.4103/1319-2442.206450
|View full text |Cite
|
Sign up to set email alerts
|

An overlap of granulomatosis with polyangiitis and eosinophilic granulomatosis with polyangiitis

Abstract: We present a case report of overlap of granulomatosis with polyangiitis (GPA; formerly known as Wegener's granulomatosis) and eosinophilic granulomatosis with polyangiitis (EGPA; formerly known as Churg-Strauss syndrome). We report a 45-year-old female who presented with rapidly progressive renal failure associated with fever, polyarthralgia, and respiratory symptoms with cytoplasmic antineutrophilic cytoplasmic antibody (ANCA) and proteinase (PR-3) antigen positivity. Computerized tomography scan of the chest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In her case, distinguishing between the vasculitides was increasingly difficult given conflicting supporting evidence including polyarthritis, pan-sinusitis, positive C-ANCA, rapidly progressive glomerulonephritis and mononeuritis multiplex. By meeting the criteria for both GPA and EGPA, she was diagnosed with polyangiitis overlapping syndrome [ 15 ]. Although previously reported, polyangiitis overlapping syndrome is not commonly recognized.…”
Section: Discussionmentioning
confidence: 99%
“…In her case, distinguishing between the vasculitides was increasingly difficult given conflicting supporting evidence including polyarthritis, pan-sinusitis, positive C-ANCA, rapidly progressive glomerulonephritis and mononeuritis multiplex. By meeting the criteria for both GPA and EGPA, she was diagnosed with polyangiitis overlapping syndrome [ 15 ]. Although previously reported, polyangiitis overlapping syndrome is not commonly recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Surendran et al identified overlap syndrome in a patient with similar features including the presence of polyarthritis, pan-sinusitis, c-ANCA positivity, rapidly progressive glomerulonephritis, and mononeuritis multiplex arguing for both EGPA and GPA [ 9 ]. The presence of a history of asthma and tissue eosinophilia favored EGPA, while the presence of nasal septal perforation and eye proptosis favored GPA.…”
Section: Discussionmentioning
confidence: 99%